Optimalisasi Google My Business untuk Meningkatkan Brand Awareness Bisnis Dekorasi - Tiwsflowers - Lutfisa, Aulia Harfa; Shiroth, Salman Fathy; Jayadin (DBESTI: Journal of Digital Business and Technology Innovation, 2025)
The growth of digital marketing has increasingly required small and medium-sized enterprises (SMEs) to optimize digital platforms to enhance brand visibility and awareness. This study aimed to examine the impact of optimizing Google My Business (GMB) on brand awareness at Tiwsflowers, a local event decoration business. The optimization strategy included updating business information, enhancing visual identity through logo and product photos, and organizing services into thematic categories. A quantitative research method with a causal-comparative approach was applied, combining A/B testing of GMB performance data and simple linear regression analysis based on a survey of 100 respondents. Results from the A/B testing revealed a 31.58% increase in website clicks after the optimization, although some other performance metrics experienced slight declines. The regression analysis indicated a positive correlation with a coefficient of 0.581 and a determination coefficient (R²) of 0.338, suggesting that 33.8% of the variance in brand awareness could be explained by GMB optimization. The T-test confirmed the statistical significance of this relationship with a p-value of 0.000. Overall, the findings demonstrated that GMB optimization made a meaningful contribution to building brand awareness and could serve as a relevant digital strategy for SMEs to strengthen their online presence. This study also offered practical implications for leveraging GMB features as part of localized marketing efforts